1995
DOI: 10.3928/1081-597x-19950101-10
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laser and Manual Removal of Corneal Epithelium for Photorefractive Keratectomy

Abstract: BACKGROUND: Photorefractive keratectomy relies on precise ablation of cornea stromal tissue to achieve a desired change in refraction. The routine technique for photorefractive keratectomy has been manual debridement of the epithelium prior to performing excimer laser ablation. We investigated whether laser ablation versus manual debridement of the corneal epithelium influences the refractive result. METHODS: A retrospective matched controlled study analyzing the refractive outcome of 46 eyes after e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…Mechanical debridement is effective and relatively straightforward but may prolong operative duration, especially in surgeons who are new to refractive surgery. Prolonged operation time can reduce stromal hydration due to evaporation, which may reduce the safety and efficacy of laser treatment [9]. Besides, it has been reported that mechanical debridement creates scratches and grooves on the Bowmanʼs membrane and the epithelium cannot be completely removed in some circumstances, leaving various amounts of the epithelium on the cornea, which may affect the depth of ablation with an excimer laser [10].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical debridement is effective and relatively straightforward but may prolong operative duration, especially in surgeons who are new to refractive surgery. Prolonged operation time can reduce stromal hydration due to evaporation, which may reduce the safety and efficacy of laser treatment [9]. Besides, it has been reported that mechanical debridement creates scratches and grooves on the Bowmanʼs membrane and the epithelium cannot be completely removed in some circumstances, leaving various amounts of the epithelium on the cornea, which may affect the depth of ablation with an excimer laser [10].…”
Section: Introductionmentioning
confidence: 99%
“…Transepithelial PRK has been used for refractive laser correction since it was introduced in the early 1990s, and became more popular after studies conducted by Aron-Rosa et al 7 and Gimbel et al 8 It is an effective and safe technique and is well tolerated by patients. 9 Published research [10][11][12] has compared clinical results between different methods of epithelial removal, including the transepithelial method using the Schwind Amaris laser platform or other two-step procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Its destruction initiates an active healing response that can lead to a loss of correction (myopic regression) from the initial refractive correction. [28][29][30] Because of the loss of best-corrected visual acuity (BCSVA), corneal scarring, and the limited predictability seen with deep surface ablation using the PRK technique, interest in the LASIK procedure has increased substantially. 31,32…”
Section: Photorefractive Keratectomymentioning
confidence: 99%